2010
DOI: 10.1590/s1415-43662010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Diferentes tecnologias de iluminação para produção de mudas de crisântemo

Abstract: A iluminação artificial usada para indução do efeito do fotoperíodo em mudas de crisântemos implica no consumo e no uso racional ou não da energia elétrica. Neste contexto, realizou-se experimento de pesquisa cujo objetivo foi analisar o uso da tecnologia de iluminação do tipo alta intensidade de descarga (HID - high intensity discharge) em substituição à de filamento incandescente na produção de mudas de crisântemos. O principal parâmetro de comparação de desempenho entre as variedades cultivadas foi a presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
2
7
0
3
Order By: Relevance
“…O consumo de energia elétrica em referência ao produto gerado representa um indicador adequado para a análise de eficiência energética, conforme resultados obtidos por Bueno & Rossi (2006), Sarubbi et al (2008; e David & Rossi (2010), que também utilizaram este índice.…”
Section: Resultsunclassified
“…O consumo de energia elétrica em referência ao produto gerado representa um indicador adequado para a análise de eficiência energética, conforme resultados obtidos por Bueno & Rossi (2006), Sarubbi et al (2008; e David & Rossi (2010), que também utilizaram este índice.…”
Section: Resultsunclassified
“…JÁCOME (2009), comparing incandescent lamp 100W (control) with sodium vapor lamp 70W, found a 54.14% reduction in demand, and comparing the control with compact fluorescent lamp 23W, the reduction was 73.76%. DAVID & ROSSI (2010) found that replacing incandescent lamps 100W with compact fluorescent lamps 23W showed a 75% reduction in electricity consumption for the production of chrysanthemum cuttings, without affecting the final output.…”
Section: Results E Discussionmentioning
confidence: 99%
“…Considering the overlap of the luminous flux, these are the points with lower levels of luminance in the experimental plot (Figure 1). No theoretical method for calculating light levels was adopted as literature reports some inconsistency between the data measured and estimated (DAVID, 2007;JORDAN & TAVARES, 2005). When using IL, CFL and ML lamps, three lines of lamps were required to meet minimum illuminance of 20 lux.…”
Section: Materials E Methodsmentioning
confidence: 99%
“…Despite the fact that the use of more energy efficient lamps has been advocated in recent years (ROSSI et al, 2010;DAVID & ROSSI, 2010;P EREIRA et al, 2012;JÁCOME et al, 2012;BORILLE et al, 2013), some aviary lighting systems are still equipped with a large number of lamps which have high potency and low efficiency. According to PEREIRA et al (2012) the replacement of incandescent bulbs (100 W) for tubular fluorescent lamps T5 (28 W) can reduce by 90.62% the energy demand in broiler poultry to a lighting level of 5 lux.…”
Section: Introductionmentioning
confidence: 99%